ANALISIS PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA PEMBELAJARAN IPAS DI SD - Sifa Lailiyah; Meirza Nanda Faradita; Holy Ichda Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the impact of the scientific approach on students' critical thinking skills in Natural and Social Sciences (IPAS) learning at Class 4C of SD Wachid Hasyim Surabaya (SD Plus), involving 16 students. The scientific approach includes observing, questioning, experimenting, reasoning, and communicating stages to encourage active student participation. This study employs a qualitative method with data collection techniques, including observation, interviews, and documentation. Observations were conducted to record students' critical thinking skills during the learning process. Interviews with the teacher and students provided in-depth insights into the application of the scientific approach. Documentation strengthened the data from observations and interviews. The results indicate that the scientific approach enhances students' critical thinking skills, as shown by their ability to formulate problems, create hypotheses, analyze data, and conclude learning outcomes. These findings offer essential insights into teaching strategies that promote critical thinking skills in elementary school students.